20x-5-5(3x+11)=0

Simple and best practice solution for 20x-5-5(3x+11)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 20x-5-5(3x+11)=0 equation:


Simplifying
20x + -5 + -5(3x + 11) = 0

Reorder the terms:
20x + -5 + -5(11 + 3x) = 0
20x + -5 + (11 * -5 + 3x * -5) = 0
20x + -5 + (-55 + -15x) = 0

Reorder the terms:
-5 + -55 + 20x + -15x = 0

Combine like terms: -5 + -55 = -60
-60 + 20x + -15x = 0

Combine like terms: 20x + -15x = 5x
-60 + 5x = 0

Solving
-60 + 5x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '60' to each side of the equation.
-60 + 60 + 5x = 0 + 60

Combine like terms: -60 + 60 = 0
0 + 5x = 0 + 60
5x = 0 + 60

Combine like terms: 0 + 60 = 60
5x = 60

Divide each side by '5'.
x = 12

Simplifying
x = 12

See similar equations:

| 5(3x+2)=7(2x+9) | | 2=2(3-2a) | | 5(x-1)+4x+3=79 | | 20p+11q+p-3q-6p= | | 2*sin*2x=-1 | | 16-6y=-9(7y-8) | | P(2)=-0.1x^5+3.8x^4+5000 | | 8x-6(2x-7)=-23 | | 8m+6n-3m+7n= | | -b^2+2b-6=0 | | 4y=7x^2-5 | | 4(2x+5)-7(x-3)= | | 8s-19=-25+6s | | 8(9+y)=7(y-3) | | sin(i)=0.4 | | 3t-3=-12+2t | | 2+2r=3-4r | | 3(n+4)=n+4 | | 14x+69=x | | 5z+3z=6z-7 | | x^3-4x^2-207x+630=0 | | 5x=88 | | 5x+2y+2z=7 | | 4(4x-8)-5=(x-3)+35 | | r+9.3=-0.5 | | (X+1)+(3x+1)+(x+1)=180 | | P(x)=-0.1x^5+3.8x^4+5000 | | 7-x=-2x-5 | | 0.4+1.5=2.2-15x | | 2n^2+2n-42=0 | | 5(3+5x)-1=89 | | 10-2a+4=32 |

Equations solver categories